CRITICAL METAPHOR ANALYSIS OF KOREAN PLASTIC SURGERY DISCOURSE IN CHOSUN ILBO: ANALISIS METAFORA KRITIS DALAM WACANA BEDAH PLASTIK DI KOREA DALAM CHOSUN ILBO - Putu Pramania Adnyana; Abdul Muta'ali; Sonya Puspasari Suganda (Jurnal Kata, 2023)
The objective of this study is to elucidate the perspectives of Korean society towards beauty by analyzing metaphorical language employed in opinion pieces pertaining to plastic surgery in the online newspaper Chosun Ilbo, spanning the years 2010 to 2019. This study used a qualitative technique, employing conceptual metaphor theory (Lakoff and Johnson 2003) and critical metaphor analysis (Charteris-Black 2004). The texts investigated included 67 opinion articles published in the online newspaper Chosun Ilbo between 2010 and 2019. tourism activities, factory activities, trade, investment, and criminal organization were identified as the five source domains employed for target domain plastic surgery in this study. In respect to beauty, the Chosun Ilbo (2010-2019) metaphorical expression sees a beautiful appearance as something that can be mass-produced in a planned design, achieved in pleasurable ways such as travelling, exchanged for money, and can be regarded as fundamental capital that gives various profit. However, a beautiful appearance is also considered as something that can be achieved through unsafe, risky, and illegal means.